Assessment and Ranking of Hot Springs Sites Representing Geothermal Resources in Southern Thailand using Positive Attitude Factors - Wipada Ngansom (Science Faculty of Chiang Mai University, 2019)
Utilization of geothermal energy resources, the heat from the Earth interior, has increased over the last decades due to climate change concerns. However, the economic potential of geothermal resources depends on various factors, e.g. heat flow, temperature gradient, reservoir temperature, flow rate, but also customer base, and environmental issues. In order to minimize financial risks during exploration and production phase and to focus on most potential sites an assessment of available geothermal sites with a subsequent ranking is required. At least 30 hot springs are located in Southern Thailand with exit temperatures varying between 40 and 80 °C. From all, seven were selected in a first stage using a 60 °C surface discharge temperature and 100 °C reservoir temperature of silica geothermometer cutoff value. In a second stage a quantitative assessment applying positive attitude factor technique was applied using numerical scores. Twenty factors in four fractions, land use, exploration, reservoir, and marketing availability, were given normalized scores from 1 to 3 based on available information and data presented. The final ranking shows that two hot springs sites, one in Ranong and one in PhangNga Province, have a good potential for further development, where advanced research budgets and investments for geothermal exploration with a focus on renewable electricity productions should be directed.